Social change for women and children - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Stamford, Conn. : JAI Press, 2000)
The contributors to this volume consider policy implications of gender research with an emphasis on its relevance for children - particularly girls; and gender inequality within a range of contexts from that of Cameroon society where basic education is an issue, to that of feminist family settings in the United States.
Introduction: social change for women and children / Vasilikie Demos, Marcia Texler Segal -- For god and community: the Unitarian female ministers' tradition and Chicago sociology, 1892-1918 / Mary Jo Deegan, Linda J. Rynbrandt -- Gender inequality in employment and retirement income: effects of marriage, industrial sector, and self-employment / Richard Hogan, Carolyn C. Perrucci, Janet M. Wilmoth -- Regulating knowledge: a critical institutional ethnography of the Indiana Manpower Placement and Comprehensive Training program (IMPACT) / C. Ditmar Coffield -- Women and democratization: lessons from Latin America / Elizabeth Cagan -- Gender and the demand for primary education in Cameroon / Martin E. Amin, George E. Fonkeng -- Creating possibilities: how young immigrant Latinas envision their futures / Jeanne D. Weiler -- Gender and youth mentoring / Katherine L. Hughes -- Gender differences in aggressive and violent behavior among African-American preadolescents: a comparison of the effects of social and psychological factors / Lois Pierce, Nancy Shields -- Girls and women growing together: integrating resources to develop the girls' circle programs / Norrine L. Ostrowski, Anna M. Silus, Beth Hossfeld, Giovanna Taormina -- Gender-related content of animated cartoons, 1930 to the present / Hugh Klein, Kenneth S. Shiffman, Denise A. Welka -- Children and gender: the case of feminist kids / Jessica Holden Sherwood, Barbara J. Risman.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social change -- United States; Women -- United States -- Social conditions; Women -- Latin America -- Social conditions; Children -- Social conditions; Women -- United States; Women -- Latin America; Child; Social Change -- United States; Gender studies, gender groups; Social research & statistics; Social Science -- Gender Studies